The Power of Data Journalism: The Effects of Data-Driven News Reports in Correcting Climate Change Misinformation - Mahmoud-Mohamed-Abdel Haleem; Hagar Talaat-Alnajjar (Communication & Society (Formerly Comunicación y Sociedad))
The alarming increase of misinformation poses a significant threat to complex issues such as climate change, especially considering the proliferation of new media, which has significantly contributed to the dissemination and reception of misinformation. The present study aimed to examine how a corrective news article featuring data visualisation influences the reduction of misconceptions and the correction of misinformation regarding climate change after readers are exposed to the stimulus. The study investigated how readers’ preexisting beliefs influence the mitigation of misconceptions when exposed to news content. This study adds to ongoing conversations about creating corrective news reports to reduce the negative impacts of misinformation surrounding climate change. A quasi-experimental study was carried out online involving 186 members of the Egyptian community. The results indicate that data journalism can reduce the cognitive dissonance that causes audiences to accept misinformation. The findings indicate that data-driven journalism utilising interactive graphs is effective in altering the public’s existing beliefs and knowledge while also demonstrating its ability to persuade and counter misinformation. The audience with low to moderate prior knowledge of climate change may demonstrate a diminished ability to thoroughly analyse and compare the information presented.